Pemberdayaan Ekonomi Pesantren Melalui Pengembangan Bisnis Usaha Mandiri - Abidin, Zainal (Universitas Nusantara PGRI Kediri, 2022)
The potential of sharia economy in Maluku is very large. Natural resources and human resources can be the main capital for the development of the Sharia economy in Maluku, as well as a catalyst for Maluku's economic growth in the future. Pondok Pesantren (Islamic Boarding Schools) are expected to participate in encouraging regional economic development with business activities in various fields. In facing the Industrial Revolution 4.0, Pondok Pesantren are expected to become a new economic force, in addition to their main function in the field of education. The seminar, entitled Pondok Pesantren Economic Empowerment through Independent Business Development, in the Salam Fest 2021 series in Ambon is expected to be able to trigger the economic acceleration of Maluku after the pandemic, as well as support the creation of regional economic recovery by strengthening Halal Value Chain through the development of MSMEs, increasing Pondok Pesantren self-reliance and increasing community participation on Sharia economics.